2012
DOI: 10.1530/joe-12-0258
|View full text |Cite
|
Sign up to set email alerts
|

Iodothyronine deiodinases: a functional and evolutionary perspective

Abstract: From an evolutionary perspective, deiodinases may be considered pivotal players in the emergence and functional diversification of both thyroidal systems (TS) and their iodinated messengers. To better understand the evolutionary pathway and the concomitant functional diversification of vertebrate deiodinases, in the present review we summarized the highlights of the available information regarding this ubiquitous enzymatic component that represents the final, common physiological link of TS. The information re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 86 publications
1
49
0
Order By: Relevance
“…In microalgae, some studies reported haloperoxidase activity (Moore et al, 1996;Murphy et al, 2000;Hill and Manley, 2009;Hughes and Sun, 2016), however, putative genes encoding putative iodoperoxidases have not been identified to date. Moreover, iodotyrosine deiodinases were only described in metazoan and bacteria (Phatarphekar et al, 2014;Taylor and Heyland, 2017) and iodothyronine deiodinases were restricted to metazoa and between social amoebae (Lobanov et al, 2007;Orozco et al, 2012;Singh et al, 2014). To increase the knowledge about iodine metabolism and oxidative defenses in T. lutea, the aims of this study were: (i) de novo assembly and characterization of a transcriptome for T. lutea cultured at high iodide concentrations; (ii) To quantify the expression patterns of antioxidant-and iodine-related genes during growth; (iii) To quantify the expression patterns of selected genes in response to iodide and iodate treatments (iv) To quantify the expression patterns of selected genes in response to H 2 O 2 and iodide treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In microalgae, some studies reported haloperoxidase activity (Moore et al, 1996;Murphy et al, 2000;Hill and Manley, 2009;Hughes and Sun, 2016), however, putative genes encoding putative iodoperoxidases have not been identified to date. Moreover, iodotyrosine deiodinases were only described in metazoan and bacteria (Phatarphekar et al, 2014;Taylor and Heyland, 2017) and iodothyronine deiodinases were restricted to metazoa and between social amoebae (Lobanov et al, 2007;Orozco et al, 2012;Singh et al, 2014). To increase the knowledge about iodine metabolism and oxidative defenses in T. lutea, the aims of this study were: (i) de novo assembly and characterization of a transcriptome for T. lutea cultured at high iodide concentrations; (ii) To quantify the expression patterns of antioxidant-and iodine-related genes during growth; (iii) To quantify the expression patterns of selected genes in response to iodide and iodate treatments (iv) To quantify the expression patterns of selected genes in response to H 2 O 2 and iodide treatments.…”
Section: Introductionmentioning
confidence: 99%
“…All deiodinases are membrane-anchored proteins of [29][30][31][32][33] kDa that share substantial sequence homology; they catalyze and sequentially remove stereo-specific iodine atoms from T4, generating active and inactive isomers of both T3 and diiodothyronine [T2]. The deiodination of T4, T3, and other iodothyronines is an integral component of TH homeostasis [3,4]. There are three deiodinases: Type 1 [D1], localized to the plasma membrane and expressed in liver, thyroid and kidney, it catalyzes removal of inner or outer ring iodine atoms in equimolar proportions to generate T3, reverse T3 [rT3], or T2 , depending on the substrate.…”
Section: De-iodinases the Balance And Control Of Thmentioning
confidence: 99%
“…136,137 For instance, Dio 1 has been localized to the kidneys and liver of fish and mammals (as well as in the mammalian thyroid gland). 138 However, hepatic T4-ORD activity is thought to be catalyzed mostly by Dio 1 in mammals and Dio 2 in fish.…”
Section: Peripheral Th Regulation and Signaling In Fishmentioning
confidence: 99%